INOVASI PRODUK ECOENZYM DAN PENCIPTAAN ALTERNATIF PRODUK TURUNANNYA UNTUK MENINGKATKAN PEMBERDAYAAN MASYARAKAT MELALUI STRATEGI MEDIA SOSIAL MARKETING: IMPLEMENTASI KEGIATAN KKN MUHAMMADIYAH AISIYAH - Anggraini, Viona; Nugraha, Handy; Putriani, Santi (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2025)
The Suboptimal waste management in Bakipandeyan Village, Sukoharjo, poses significant challenges to the environment and public health. The community’s tendency to dispose of waste without considering its potential benefits is one of the primary causes. This community service program aims to empower residents by converting organic waste into economically valuable products such as ecoenzym and soap bars, while enhancing digital marketing skills. The methods employed include socialization and training on ecoenzym production from fruit peels, soap-making workshops, and the introduction of social media marketing strategies. The program outcomes indicated improved understanding and skills among the community in processing organic waste into high-value products. Additionally, digital marketing training encouraged residents to utilize social media as a promotional tool, enabling their products to reach wider markets. This program successfully motivated the community to independently and sustainably manage waste, contributing to increased economic welfare and environmental sustainability. In conclusion, community empowerment through training, product innovation, and digital marketing proved effective in raising environmental awareness, fostering better waste management practices, and creating new business opportunities for the community